THE STUDENT’S PERCEPTION OF QUIZIZZ.COM USED AS THEIR ENGLISH LEARNING AND EVALUATION MEDIA - Mahlufatun Nisa (ELLTER Journal, 2022)
This study aimed to investigate the students' perceptions of Quizizz.com used as their English learning and evaluation media. The subject of the study was 50 eighth-grade students of MTs Roudhotul Muhibbin Bekasi. The research design of this study was descriptive quantitative by applying closed-ended questionnaire that is categorized as a survey instrument. The data was then analyzed through MS. Excel calculation system. The result showed positive perception of the students toward using Quizizz as their English learning and evaluation media. The students also responded that Quizizz has interesting features and displays, is easy to use, and had the motivation and interest in learning English. However, most students were still hesitant to use Quizizz.com in the future due to some factors that need to be investigated later on.